2023
DOI: 10.1200/jco.22.01239
|View full text |Cite
|
Sign up to set email alerts
|

Contralateral Breast Cancer Risk Among Carriers of Germline Pathogenic Variants inATM,BRCA1,BRCA2,CHEK2, andPALB2

Abstract: PURPOSE To estimate the risk of contralateral breast cancer (CBC) among women with germline pathogenic variants (PVs) in ATM, BRCA1, BRCA2, CHEK2, and PALB2. METHODS The study population included 15,104 prospectively followed women within the CARRIERS study treated with ipsilateral surgery for invasive breast cancer. The risk of CBC was estimated for PV carriers in each gene compared with women without PVs in a multivariate proportional hazard regression analysis accounting for the competing risk of death and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
0
6

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 53 publications
4
39
0
6
Order By: Relevance
“…Our understanding of subsequent BCs and contralateral BCs is evolving, and data show that females with a PV in BRCA1, BRCA2, PALB2, TP53, or the CHEK2 1100del PV have a high risk of a subsequent and/or contralateral BCs in particular, if their first BC was diagnosed at a young age [1,3,[21][22][23][24]. Moreover, about one-fifth of subsequent BCs (22.5%, 86/383) were in females with a PV in a BC risk gene.…”
Section: Discussionmentioning
confidence: 99%
“…Our understanding of subsequent BCs and contralateral BCs is evolving, and data show that females with a PV in BRCA1, BRCA2, PALB2, TP53, or the CHEK2 1100del PV have a high risk of a subsequent and/or contralateral BCs in particular, if their first BC was diagnosed at a young age [1,3,[21][22][23][24]. Moreover, about one-fifth of subsequent BCs (22.5%, 86/383) were in females with a PV in a BC risk gene.…”
Section: Discussionmentioning
confidence: 99%
“…This lack of association with ATM in our cohort is in contrast with a study that suggested a strong association based on 4 of 33 (12%) detection rates in women with bilateral breast cancer 13. The lack of association is further corroborated by a large follow-up study in the Cancer Risk Estimates Related to Susceptibility (CARRIERS cohort, which again found no association with ATM but did find an association for the other main genes BRCA1/2 , CHEK2 and PALB2 , although only the PALB2 PV carriers with ER− breast cancer had elevated risks 14. A further study assessing relative risks of breast cancer genes compared with population controls in bilateral disease5 also found a strong association with PALB2 in 252 bilateral cases with an OR of 16.19 (5.48–34.22) but no clear association with CHEK2 or ATM with relative risks similar to the twofold and threefold risks found for breast cancer as a whole from large case–control studies 15 16.…”
Section: Discussionmentioning
confidence: 89%
“…Indeed, germline likely pathogenic or pathogenic variants (LPV/PV) in PALB2 are associated with an increased risk of breast and pancreatic cancer, 3 while evidence for association with ovarian cancer is conflicting. It is estimated that 0.6%–3% of patients with BC harbor an LPV/PV in PALB2 4 and approximately 1% of patients with triple‐negative BC (TNBC) carry such a mutation 5,6 . As already observed in g BRCA ‐associated BC, 7–9 PARP inhibitors showed promising activity in patients carrying PALB2 LPV/PV in two small phase 2 studies 10,11 .…”
Section: Introductionmentioning
confidence: 87%